Penerapan Arsitek Biofilic Pada Perancangan Kawasan Wisata Edukasi Aquaponik Di Malang - Mahardika, Aringga Rani; Kusumaningayu, Intan (Peneliti.net, 2024)
The aim of this research is to find out and analyze the role of biophilic architecture in collecting data in the form of study literature that is in accordance with the research discussion. The data used includes general data consisting of location, village/sub-district, sub-district, provincial district and land area. The results of the research show that this aquaponics educational tourism area has great potential to improve the economy in Malang. Apart from that, it also has the potential to become an attraction for local and foreign tourists. This tourist area can also inspire tourists to try farming using the simple aquaponics method in their own homes. The application of biophilic architecture in this design is in the